Teacher Leadership Models in Developing Cognitive Ability in Early Children - Mukaffan Mukaffan; Akmal Mundiri; Ninik Wahyuningsih; Siti Romla (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
The purpose of this study was to determine the teacher's leadership model in an effort to develop early childhood cognitive abilities in RA Hidmatul Hikam, Alassumur Lor. This research uses a qualitative approach with a case study type. The technique of collecting data from the process of observation and interviews with the principal, Deputy Head of Curriculum, homeroom teacher for grades A and B. Data analysis techniques using the Miles and Huberman Interactive Model with data reduction activities, data presentation, and drawing conclusions. Data validity with source and technique triangulation process. The leadership model of the teachers at RA Hidmatul Hikam, Alassumur Lor refers to the participatory-democratic leadership model. This leadership model includes two main characteristics, namely the concept of aspirational management, and broad-minded personal. The teacher leadership model shown in this study describes a teacher figure who emphasizes communication, equalizes subordinates (students), synchronizes learning interests and goals in terms of personal interests and goals, and makes decisions systematically according to the opinions, complaints, and problems of subordinates (students). . So that in learning, these two characteristics become an effort to develop students' cognitive development collaboratively without any pressure.